(untitled) (Caligrama: Revista de Estudos Românicos, 2012)
Resumo: Neste artigo, analisamos a ocorrência das formas pronominais me e te em estruturas de redobro. Argumentamos que, em alguns falares mineiros, essas formas estão sendo reanalisadas como prefixos de concordância para os traços de pessoa [+falante] e [+destinatário]. O trabalho se desenvolve dentro da abordagem minimalista. Lançamos mão também de alguns conceitos de gramaticalização. Palavras-chave: Pronomes pessoais; clíticos redobros; concordância; reanálise; gramaticalização. Abstract: This study examines the occurrence of the pronoun forms me and te in clitic doubling structures. We argue that in some nonstandard Brazilian Portuguese dialects from the state of Minas Gerais, these forms are being reanalyzed as prefixes of agreement for the person features [+speaker] and [+addressee]. The analysis is developed within the minimalist approach. We used also some concepts of grammaticalization. Keywords: Personal pronouns; clitic doubling; agreement; reanalysis; grammaticalization.